REVERENCE MORALS PROFILE OF ŪLÃ, WUSTHÃ, AND ULYÃ SANTRI AT PONDOK PESANTREN ANNUQAYAH, MADURA ISLAND - Arina Mufrihah; Imaniyatul Fithriyah; Anna Aisa; Iswatun Hasanah (Universitas Pendidikan Indonesia, 2023)
This study aims to explore takzim (reverence) morals profile of Islamic boarding school students (santri of pondok pesantren) at Pondok PesantrenAnnuqayah, Sumenep. Data resources of this research were santri of Lubangsa Area especially Lubangsa Putra which having a number of 1.174 santri. Respondents were selected using stratified sampling method based on stratum of Class Ūlã (beginner class), Class Wusthã (middle class), and Class Ulyã (advanced class). Through the slovin’s formula, there were selected 94 santri ūlã, 150 santri wusthã, and 106 santri ulyã. The data were collected through survey method and analyzed by Kruskal-Wallis Test dan Mann Whitney U Test. Results of the study reveal that there is no significant difference in morals of ta’dzim among santri ūlã, wusthã, and ulyã. The contribution of this study is that the ta’dzim value as reference/ basis/standard of ideal personality and behavior of santri. Furthermore, the study results are also input for developing a foundation for counseling relationship based on the wisdom of pondok pesantren.